2017
DOI: 10.15210/jonah.v7i1.9263
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of depressive symptoms among pregnant adolescents

Abstract: Objetivo: verificar sintomas depressivos em gestantes adolescentes em unidade básica de saúde. Métodos: Cinquenta e cinco adolescentes grávidas foram entrevistadas na unidade de saúde. Para a coleta de dados, foram utilizados dois instrumentos: um para dados sociais, demográficos, obstétricos, relações familiares e eventos de violência, e outro para avaliar os sintomas depressivos - Inventário de Depressão de Beck. Resultados: 10,9% das entrevistadas tinham história prévia de depressão ou ansiedade e 3,6% apre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 3 publications
(3 reference statements)
0
3
0
Order By: Relevance
“…The results obtained by Masselink et al (2018) showed that low self-esteem may make early adolescents more vulnerable to develop depressive symptoms in late adolescence and early adulthood, whereas young adolescents who experience low self-esteem are certainly not predisposed to experience depressive symptoms during development into adulthood. Research on depressive symptoms in adolescents is relevant to the extent that they can propose effective prevention, early detection, assessment, and intervention alternatives for the management of such a clinical condition in an age group that has been shown to be vulnerable to it (Costa et al 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results obtained by Masselink et al (2018) showed that low self-esteem may make early adolescents more vulnerable to develop depressive symptoms in late adolescence and early adulthood, whereas young adolescents who experience low self-esteem are certainly not predisposed to experience depressive symptoms during development into adulthood. Research on depressive symptoms in adolescents is relevant to the extent that they can propose effective prevention, early detection, assessment, and intervention alternatives for the management of such a clinical condition in an age group that has been shown to be vulnerable to it (Costa et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Adolescence is the transition period between childhood and adulthood characterized by the need for social integration, the search for self-affirmation and individual independence, in addition, to the consolidation of sexual identity and conflicting emotions (Costa et al, 2018). Adolescence is a stage of instabilities and physical, socio-affective and behavioral changes, highlighted by an emotional responsiveness to stress and an increase in the so-called exploratory behaviors, which enhances the development of the individual, but can cause psychological problems if exceeded (Bermúdez, 2017).…”
Section: Depression and Adolescencementioning
confidence: 99%
See 1 more Smart Citation